Development Evaluation in Times of Turbulence: Dealing with Crises That Endanger Our Future - Rist, RayC. (World Bank, 2015)
The presence of turbulence in multiple areas of our society--food, fuel, and finances-being but three critical areas presently being impacted means that long-held assumptions are no longer true, that the past is not prologue, and that the future is not clear. And enter into this unstable present the discipline of evaluation-a discipline formed and shaped in the past fifty years of stability, little turbulence, and strong assumptions that everything will go according to plan. If things do not go well, it is because of either a poor theory of change on how to bring about positive outcomes, or weak efforts at implementation. It is not because of the stormy present upsetting our quiet past. As it is, conventional evaluation behavior and beliefs are ill suited for these times. The transformational nature of the 'Arab Spring' is just one arena in which it is clear that a business as usual approach to evaluation is entirely inappropriate.